Pengaruh Cerita Pendidikan “Semut Dan Jangkrik” Terhadap Perkembangan Moral Anak Usia 5-6 Tahun - Afifa, Nida; Handayani, Peny Husna (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2024)
Fable story books can be used as a learning activity for children and as an instillation of children's moral behavior which is given by teachers to children from an early age as a trigger for children when they be have badly. Inthiscase, there is a lack of storytelling activities in instilling moral values in children. This research aims to determine the influenceof the story